2020
DOI: 10.1002/anzf.1407
|View full text |Cite
|
Sign up to set email alerts
|

Not ‘Just a Talking Head’: Experiences of Australian Public Mental Health Clinicians Implementing a Dialogical Family Therapy Approach for Young People with Severe Mental Health Concerns

Abstract: The evidence for efficacy of family‐based approaches for psychological problems is extensive, although model‐specific effects have not been established. However, implementation of family therapy approaches in tertiary mental health settings has been challenging due to factors such as negative staff attitudes and difficulties engaging families. Open Dialogue is an emerging network‐based therapy that has a focus on genuine collaboration, flexibility, authenticity, and openness. This study describes the experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
(108 reference statements)
1
9
0
Order By: Relevance
“…In Dawson et al’s (2021) description of a network meeting, a young person at the center of concern had some trepidation before and during the meeting, but she and her family found it meaningful to share their concerns about each other. In the study by Sidis et al (2020), young clients expressed being nervous before and after meetings but being able to say what they wanted to say. Staff members’ reflections were appreciated as they shared their thinking about the situation (Sidis et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Dawson et al’s (2021) description of a network meeting, a young person at the center of concern had some trepidation before and during the meeting, but she and her family found it meaningful to share their concerns about each other. In the study by Sidis et al (2020), young clients expressed being nervous before and after meetings but being able to say what they wanted to say. Staff members’ reflections were appreciated as they shared their thinking about the situation (Sidis et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The studies of staff members’ experiences noted that Open Dialogue approaches had given staff members more opportunities for responding authentically, and for assisting clients and families/social networks. Sidis et al (2020) found that working with Open Dialogue was very much aligned with staff members’ personal values. They valued being more authentic in their approach and the privileging of the families’ perspectives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last two decades Open Dialogue has been implemented in healthcare services across Scandinavia (Buus et al, 2017), and has been adapted in Australia, the United Kingdom, Italy, Germany, and the United States of America. The approach has gradually been extended to mental health services for people with issues other than psychosis, such as young people in psychiatric crisis (Buus et al, 2019) or young people diagnosed with eating disorders or mood disorders (Sidis et al, 2020). Extending into community services, this study explored the experiences of Open Dialogue network meetings following their implementation in an Australian women’s shelter.…”
Section: Aims Of the Studymentioning
confidence: 99%